2013
DOI: 10.3354/meps10196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in a moulting colony of southern elephant seals in comparison with breeding colonies

Abstract: Southern elephant seals Mirounga leonina migrate seasonally between pelagic foraging areas in the Southern Ocean and breeding and moulting sites on subantarctic islands. Here we characterized genetic diversity of the elephant seal moulting colony from King George Island (KGI), South Shetlands Archipelago, in comparison with breeding colonies described in earlier studies. Although KGI serves as a breeding site, the numbers of elephant seals are up to 3 times higher during the moulting season, suggesting post-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Previous studies have shown lower genetic diversity in the Península Valdés and Macquarie Island breeding stocks in both mtDNA and microsatellites (Slade et al 1998;Fabiani 2002;Chauke 2008), whereas the study by Hoelzel et al (1993) investigated only mtDNA. In contrast, genetic diversity was higher within the South Georgia stock (South Georgia, Elephant Island, Sea Lion Island, and Falkland Islands seals), and the Kerguelen and Heard Island stock (Heard Island and Marion Island seals), as seen from mitochondrial studies (Hoelzel et al 1993) and other studies that investigated genetic diversity in both mtDNA and microsatellites (Slade et al 1998;Chauke 2008;Bogdanowicz et al 2013). Evidence of sex-biased dispersal was found in previous studies where male-biased gene flow and male dispersal occurred more than in females (Slade et al 1998;Fabiani 2002;Chauke 2008;Bogdanowicz et al 2013;Corrigan et al 2016).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown lower genetic diversity in the Península Valdés and Macquarie Island breeding stocks in both mtDNA and microsatellites (Slade et al 1998;Fabiani 2002;Chauke 2008), whereas the study by Hoelzel et al (1993) investigated only mtDNA. In contrast, genetic diversity was higher within the South Georgia stock (South Georgia, Elephant Island, Sea Lion Island, and Falkland Islands seals), and the Kerguelen and Heard Island stock (Heard Island and Marion Island seals), as seen from mitochondrial studies (Hoelzel et al 1993) and other studies that investigated genetic diversity in both mtDNA and microsatellites (Slade et al 1998;Chauke 2008;Bogdanowicz et al 2013). Evidence of sex-biased dispersal was found in previous studies where male-biased gene flow and male dispersal occurred more than in females (Slade et al 1998;Fabiani 2002;Chauke 2008;Bogdanowicz et al 2013;Corrigan et al 2016).…”
Section: Introductionmentioning
confidence: 91%
“…The genetic structure and genetic diversity of the breeding colonies of SES have been investigated previously using mitochondrial DNA (mtDNA) and microsatellites (Hoelzel et al 1993;Slade et al 1998;Fabiani 2002;Chauke 2008;Bogdanowicz et al 2013). Previous studies have shown lower genetic diversity in the Península Valdés and Macquarie Island breeding stocks in both mtDNA and microsatellites (Slade et al 1998;Fabiani 2002;Chauke 2008), whereas the study by Hoelzel et al (1993) investigated only mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…We collected a total of 201 additional sequences of the mitochondrial control region from GenBank (Hoelzel et al 1993; Slade et al 1998; Fabiani 2002; Chauke 2008; Curtis et al 2009; Bogdanowicz et al 2013; Zappes et al 2017). These comprised 191 sequences from southern elephant seals and 10 sequences from Weddell seals ( Leptonychotes weddellii ),which we included as an outgroup because they belong to the same subfamily of Phocidae (Slade et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic structure of the breeding colonies of SES have been investigated previously (Hoelzel et al 1993; Slade et al 1998; Fabiani 2002; Chauke 2008; Bogdanowicz et al 2013). However, there remains a gap in our knowledge regarding the natal origins of seals at moulting sites such as Davis Base, where seals potentially from multiple breeding sites aggregate (Bester 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Within the molt period, though, there is considerable individual variability in timing. In part, this is related to age, sex and internal/ endocrine processes (Bogdanowicz et al 2013). The annual molt occurs sequentially through age-sex classes: first juveniles molt, then adult females, and finally adult males (Boulva and McLaren 1979, Thompson and Rothery 1987, Daniel et al 2003, Cronin et al 2014.…”
mentioning
confidence: 99%